Study and description of the Record of Settlement Juros Convent of Santa Clara of Medina de Pomar (1432-1882) - Viretto, Paolo; Sánchez Domínguez, Mª del Carmen (Revista General de Información y Documentación, 2016)
Based on an attentive bibliographical revision and the work of a multilevel stand-ardized description, this paper seeks to carry out an historical and documentary study that has as its subject the documentary collections in the care of public archives. Taking from the documentation that proceeds from the Fondo Antiguo de Hacienda and is preserved in the AGA, the case of the “Record of the Settlement of Property Rights of the Convent of Saint Clare of Medina de Pomar (1432-1882)” has been chosen with the aim of applying the ar-chival techniques and to value a part of the historical patrimony preserved in state archives.